Электромагнитные экраны для снижения индукции магнитного поля промышленной частоты на объектах энергетики - Резинкина, М.М.; Гринченко, В.С. (Технічна електродинаміка, 2012)
The problem of magnetic field induction mitigation on power objects personnel workplaces located close to electrical pathways has been considered. Comparison of metal required for shields for the cases of electrical pathways and protected area screening has been carried out. By computer modeling of magnetic field induction distribution in the system «three-phase electrical pathway?electromagnetic shield» has been calculated. Configurations of the electromagnetic shields reducing industrial frequency magnetic field induction to sanitary proved level have been offered.